The Third Order Variant Narayana Codes and Some Straight Lines Corresponding to These - Çağla Çelemoğlu (Düzce Üniversitesi Bilim ve Teknoloji Dergisi, 2022)
In this study, firstly, we examined the second order variant Narayana codes and we got some results from the tables were displayed by Das and Sinha. Then, we studied on the third order variant Narayana code and we displayed these codes for some k positive integers and with tables. Also, we got some results from the tables. Then, we compared the results that we obtained from the tables for the third order variant Narayana universal code and the second order variant Narayana universal code in terms of cryptography. We found that third order variant Narayana universal code are much more advantageous than the second order variant Narayana universal code. Finally, we obtained some straight lines which yielding the some the third order Narayana codewords by considering (u,k) as a point in the (x,y) plane, from these tables.